Analysis and Design of Reinforced Concrete Beam-column Joint Using King Cross Steel Profile. (2017) - Kadarningsih, Rahmani; Satyarno, Iman; Muslikh,; Triwiyono, Andreas
Abstract: The limitation or the neglecting of concrete role in resisting the shear stress causes the need of high amount of steel bars reinforcement in beam-column joints. This will cause problem if the steel bars reinforcement congestion occurs where the steel bars reinforcement may not be easy to be installed. This paper discuss the analysis and design of king cross steel profile to be implemented as alternative reinforcement in reinforced concrete beam-column joints. With the simplifying assembling the use of king-cross steel profile implants at beam-column-joints as a shear reinforcement could be expected to replace the transversal reinforcement and enhance the joint shear strength. Therefore various arrangements of beam-column reinforcement are studied analytically.